Characterization of mangrove mudflat sediment contamination by fecal bacteria and trace metals: A multivariate assessment in equatorial marine protected areas in Gabon, Western Central Africa - Johann Ludovic Martial Happi; Aimé Roger Nzigou; Gauthier Schaal; Marie-Laure Rouget; Rolf Gael Mabicka Obame; François Le Loc’h; Jean-Daniel Mbega; Christophe Leboulanger; Patrick Mickala (PLoS ONE, 2025)
Among the most productive ecosystems worldwide, mangroves contribute to global carbon sequestration and play a pivotal role for many species, including supporting the sustainable provision of intertropical fisheries resources. Despite the many essential ecosystem services they provide, mangrove ecosystems are facing increasing anthropogenic pressure, primarily because they develop in littoral areas where human activities are rapidly expanding, causing deforestation, urban extension and pollution. Mangroves cover over 1,700 km² of Gabon’s coastline, stretching within protected zones or located alongside populated areas, raising concerns about the potential impact of pollution. This study assessed pollution levels in mangrove surface sediments from 24 stations in the capital city of Libreville and the two adjacent Marine Protected Areas (MPAs), Akanda and Pongara, where human impact has not been fully characterized. From 2021 to 2023, we measured chlorophyll a, fecal indicator bacteria (FIB: Escherichia coli and fecal streptococci) and six trace metals (As, Cd, Cr, Cu, Pb and Zn). Our results show that while Pongara National Park remains relatively pristine, human influence has resulted in significant contamination of sediments by FIB and trace metals, with Cu, Pb and Zn being associated with boat traffic and fuel spills. Chlorophyll a at the surface of sediments, indicative of microphytobenthic biomass, reflect the eutrophication from urban discharge. Spatial differences in contamination patterns are significant between Libreville and Akanda, and between Akanda and Pongara parks (p < 0.05), but not significant between Libreville and Pongara National Park (p > 0.05), suggesting a possible rapid dispersion of urban pollution. Despite localized pollution, contamination levels remained generally low, suggesting that patterns are influenced more by the specific characteristics of each area than by MPA status. This study provides a first assessment of pollution pressure on mangrove tidal flats within protected areas in Gabon, emphasizing that the success of MPAs could be enhanced through contamination monitoring to achieve long-term conservation goals.